Synthesis, characterization and spectroscopy of the europium doped lanthanum trimetaphosphate - Stucchi, Elizabeth Berwerth [UNESP]; De Castro, Andrea M. [UNESP]; Couto Dos Santos, Marcos A. [UNESP]; Melnikov, Petr [UNESP] (Elsevier, 1998)
Orthorhombic modification of europium doped lanthanum trimetaphosphate has been prepared. The compound was obtained by precipitation of rare earth chloride solution with trimetaphosphoric acid. The characterizations were made using X-ray diffractometry, chemical analysis and infrared spectroscopy. Excitation and emission spectra were recorded at liquid nitrogen and room temperatures. Assignments of the 5D0→7FJ (J=0, 1, 2, 3, 4, 5) transitions were made and an unusual high 5D0→7F4 transition intensity with six split lines has been observed. Structural distortion of the crystal lattice may be caused by the Eu3+ ion inclusion. The simple overlap model was applied for the calculation of the total splitting of the 5D0→7F1 transition, the 5D0→7F0/5D 0→7F2 transition intensity ratio and the Ωλ (λ=2.4) intensity parameters. Theoretical predictions showed to be in good accordance with the experimental data. © 1988 Elsevier Science S.A.
Keywords: F-f intensities; Lanthanide trimetaphosphate; Orthorhombic structure; Chemical modification; Chlorine compounds; Crystal lattices; Doping (additives); Electron transitions; Europium; Infrared spectroscopy; Mathematical models; Phosphoric acid; Precipitation (chemical); Synthesis (chemical); X ray crystallography; Lanthanum trimetaphosphate; Simple overlap model; Lanthanum compounds